Religion and the Political Process: the Fourth Wave of Democratization - R. N. Lunkin (Международная аналитика, 2021)
The article analyzes the role of religion in socio-political processes in Europe, in the post-Soviet space, and more broadly in the Western world. The structural and functional approach, methods of sociological and political analysis of the religious factor as a political phenomenon are applied. The purpose of the study is to analyze the role of religion (mainly Christian churches) in democratic processes on the example of the EU member states and the post-Soviet space. Special attention is paid to the participation of various Christian churches in socio-political transformations, conflicts and “orange” revolutions, as well as to the opposition of religion to the ideology of modern liberal democracy from the standpoint of traditionalism (identity). It is concluded that religion has become an important marker of a global phenomenon that can be called the “fourth wave” of democratization (following the periodization of S. Huntington). If within the framework of the third wave, religion was one of the elements and at the same time objects of democratization, then since the 2000s religion is the main impulse factor of the entire process of traditionalist democratization in social, political and cultural dimensions. The civic activity of believers corrects liberal democracy, makes it more “moral,” and not archaic. The merit of religion is that it has clearly defined the boundaries beyond which the democracy of the future should not be transgressed: the recognition of the right to traditional moral foundations for entire societies and states along with the usual liberal freedoms, i.e., equality of all races and peoples, the value of every person, the freedom of speech.